In dogs undergoing anaesthesia do pre-anaesthetic gastroprotectants reduce gastro-oesophageal reflux? - Barry, Leanne (Veterinary Evidence, 2020)
PICO question In dogs undergoing anaesthesia do pre-anaesthetic gastroprotectants reduce gastro-oesophageal reflux? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed Five papers were critically reviewed. There was a randomised prospective study, two randomised blinded prospective studies, randomised non-blinded prospective study and a randomised, double blinded and placebo-controlled prospective study. Strength of evidence Moderate Outcomes reported Evidence of high quality suggests omeprazole or cisapride with esomeprazole decrease the incidence of gastro-oesophageal reflux (GOR) in the anaesthetised dog. In addition, a study of lower quality showed that continuous infusion of metoclopramide at a higher than normal dose rate decreased the incidence of GOR. Conclusion Omeprazole or cisapride with esomeprazole decreases the incidence of GOR in the anaesthetised dog. How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision-making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care